2007
DOI: 10.1186/1752-1947-1-104
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical embolism, deep vein thrombosis, pulmonary embolism in a patient with patent foramen ovale: a case report

Abstract: IntroductionCoexistence of pulmonary embolism and systemic arterial embolism suggest the diagnosis of paradoxical embolism which suggests the presence of intracardiac defects such as patent foramen ovale (PFO).Case presentationA 42 year old man was found to have a paradoxical embolism in the systemic arterial circulation, in the setting of pulmonary embolism and deep vein thrombosis (DVT) in the lower extremities.ConclusionParadoxical embolism and intracardiac shunt should be immediately considered in a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
11
0
4
Order By: Relevance
“…The mechanism of the renal infarction in our case was considered that transiently increased right arterial hypertension, due to acute pulmonary embolism induced continuous opening of PFO and permitted a passage of the thrombi in deep vein into the arterial system 11). It should also be noted that though there have been several case reports of systemic PDEs with PTE associated with PFO,7)8)13) cases of non-cerebral, systemic PDEs, associated with PFO, are relatively lower than for cerebral PDEs. One report showed that only 2.9% of patients with PFO presented with a presumptive diagnosis of systemic embolism,14) though when patients with major pulmonary embolism have PFO, the incidence of peripheral artery embolisms, can significantly be increased (up to 15%) 15)…”
Section: Discussionmentioning
confidence: 70%
“…The mechanism of the renal infarction in our case was considered that transiently increased right arterial hypertension, due to acute pulmonary embolism induced continuous opening of PFO and permitted a passage of the thrombi in deep vein into the arterial system 11). It should also be noted that though there have been several case reports of systemic PDEs with PTE associated with PFO,7)8)13) cases of non-cerebral, systemic PDEs, associated with PFO, are relatively lower than for cerebral PDEs. One report showed that only 2.9% of patients with PFO presented with a presumptive diagnosis of systemic embolism,14) though when patients with major pulmonary embolism have PFO, the incidence of peripheral artery embolisms, can significantly be increased (up to 15%) 15)…”
Section: Discussionmentioning
confidence: 70%
“…This predisposed him to the development of lower extremity deep vein thrombosis and large bilateral PE [ 1 ]. The development of arterial embolus to the left arm was made possible by a large PFO and has been cited several times in the literature [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors associated with embolic recurrence include atrial septal aneurysm, high shunting volume, and shunting at rest. Other risk factors include large PFO (more than 3.4 mm), higher mobility of the PFO valve, a well developed Eustachian valve, a Valsalva maneuver immediately prior to event, and a history of recurrent embolic events [13] . Bissessor et al reviewed 70 percutaneous PFO procedures prospectively.…”
Section: Discussionmentioning
confidence: 99%